Exploring the interplay between food security and antenatal care utilization among pregnant women in Southern Ethiopia: Insights from an institution-based cross-sectional study - Gemeda Wakgari Kitil; Lema Fikadu Wedajo; Gizu Tola Feyisa; Bekem Dibaba Degefa; Shambel Negese Marami; Agmasie Damtew Walle; Alex Ayenew Chereka; Dagne Deresa Dinagde (Elsevier, 2024)
Background: Ensuring the satisfaction of pregnant women with antenatal care is crucial for positive pregnancy outcomes and their engagement with emerging technologies and alternative care models. Maintaining high satisfaction during the antenatal period significantly impacts the well-being of both the expectant mother and the unborn child. Despite the recognized importance of antenatal care satisfaction, comprehensive information on satisfaction levels and influencing factors in the specific study area is lacking. Therefore, this study aims to assess antenatal care service satisfaction and associated factors among pregnant women in Arba Minch town, southern Ethiopia. Methods: We conducted an institution-based cross-sectional study among 418 pregnant women from December 2022 to January 30, 2023, using a systematic sampling method. Data were collected using the Kobo Toolbox and analyzed with SPSS Version 26. The threshold for statistical significance was set at a p-value of less than 0.05. Results: Out of 418 participants, 54.3% (95% CI=49.4-60.4) expressed satisfaction with antenatal care services. Factors significantly associated with women's satisfaction included: being unable to read and write (AOR=2.37; 95% CI: 1.97-3.80), being aged 25-29 years (AOR=3.20; 95% CI: 1.65-6.22), receiving antenatal care at a hospital (AOR=1.81; 95% CI: 1.05-3.12), having a previous history of antenatal visits (AOR=2.59; 95% CI: 1.26-5.30), a monthly income of 2500-5000 ETB (AOR=1.44; 95% CI: 1.21-3.94), waiting times of less than 30 min (AOR=2.59; 95% CI: 1.52-4.41), maintaining a positive attitude towards antenatal care (AOR=2.50; 95% CI: 1.05-3.65), and having a secure food source (AOR=2.06; 95% CI: 1.13-3.78). Conclusion: Over 54% of participants were satisfied with antenatal care services. To improve satisfaction levels, recommended strategies include enhancing healthcare infrastructure, establishing maternity waiting areas, reducing waiting times, and expanding services to remote areas.